2023
DOI: 10.1186/s12903-023-02969-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral candidiasis and cigarette, tobacco, alcohol, and opium consumption in Rafsanjan, a region in the southeast of Iran

Abstract: Background We investigated the association between oral candidiasis prevalence and cigarette, tobacco, alcohol, and opium consumption in Rafsanjan, a region in the southeast of Iran. Methods This cross-sectional study was conducted using the data of Oral Health Branch of Rafsanjan Cohort Study (OHBRCS) as a part of the Rafsanjan Cohort Study (RCS). RCS included in Prospective Epidemiological Research Studies in IrAN (PERSIAN) was begun in 2015 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In a recent study by Navabi et al, the prevalence rate of oral candida fcolonization was 38.7% among opium users and cigarette smokers in southeastern Iran 20 . Conversely, Khalili et al reported a low prevalence (7.94%) of oral candidiasis in individuals using cigarettes, tobacco, alcohol, and opium in Rafsanjan, a region in southeastern Iran 21 . In another study conducted in Spain, Sheth et al demonstrated that around 35% of volunteers (37 individuals) harbored Candida species in their oral cavities 22 .…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study by Navabi et al, the prevalence rate of oral candida fcolonization was 38.7% among opium users and cigarette smokers in southeastern Iran 20 . Conversely, Khalili et al reported a low prevalence (7.94%) of oral candidiasis in individuals using cigarettes, tobacco, alcohol, and opium in Rafsanjan, a region in southeastern Iran 21 . In another study conducted in Spain, Sheth et al demonstrated that around 35% of volunteers (37 individuals) harbored Candida species in their oral cavities 22 .…”
Section: Discussionmentioning
confidence: 97%